Hyperoxemia and long-term outcome after traumatic brain injury - Raj, Rahul (BioMed Central, 2013)
INTRODUCTION: The relationship between hyperoxemia and outcome in patients with traumatic brain injury (TBI) is controversial. We sought to investigate the independent relationship between hyperoxemia and long-term mortality in patients with moderate-to-severe traumatic brain injury. METHODS: The Finnish Intensive Care Consortium database was screened for mechanically ventilated patients with a moderate-to-severe TBI. Patients were categorized, according to the highest measured alveolar-arterial O(2) gradient or the lowest measured PaO(2) value during the first 24 hours of ICU admission, to hypoxemia (<10.0 kPa), normoxemia (10.0 to 13.3 kPa) and hyperoxemia (>13.3 kPa). We adjusted for markers of illness severity to evaluate the independent relationship between hyperoxemia and 6-month mortality. RESULTS: A total of 1,116 patients were included in the study, of which 16% (n = 174) were hypoxemic, 51% (n = 567) normoxemic and 33% (n = 375) hyperoxemic. The total 6-month mortality was 39% (n = 435). A significant association between hyperoxemia and a decreased risk of mortality was found in univariate analysis (P = 0.012). However, after adjusting for markers of illness severity in a multivariate logistic regression model hyperoxemia showed no independent relationship with 6-month mortality (hyperoxemia vs. normoxemia OR 0.88, 95% CI 0. 63 to 1.22, P = 0.43; hyperoxemia vs. hypoxemia OR 0.97, 95% CI 0.63 to 1.50, P = 0.90). CONCLUSION: Hyperoxemia in the first 24 hours of ICU admission after a moderate-to-severe TBI is not predictive of 6-month mortality.